An exploratory study of social disclosure practices of Islamic banks in Malaysia - Nur Haniza Binti Zaharan (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2012)
This study explores the social disclosure aspects of fully-fledged Islamic banks in Malaysia. Social disclosure is a part of corporate disclosure taken for granted by many. Since Islamic banks are governed by Shariah principles, they have responsibility not only to their shareholders and customers, but also to other stakeholders and the society. Hence, their annual reports should be able to demonstrate their commitment to Shariah principles and their accountability to the society. In particular, the study seeks to explore the current social disclosure performance of Islamic banks in Malaysia. It also examines the factors affecting social disclosure and the social disclosure performance of Malaysia's first Islamic bank, Bank Islam Malaysia Berhad (BIMB). In this study, annual reports of 12 fullyfledged Islamic banks in Malaysia were analysed from year 2008 to 20 I 0 using benchmark social disclosure items. This study specifically developed the Islamic Bank Social Disclosure Index (IBSDI) for the purpose of conducting analyses on the Islamic banks' social disclosure. Consequently, this study found that the level of social disclosure by Islamic banks in Malaysia is generally reasonable, although there are much rooms for improvements especially in areas such as 'Unlawful Transactions', 'Products', 'Zakah', ·Late Repayments and Insolvent Clients', 'Charitable and Social Activities', and 'Other Aspects of Community Involvement'. Hence, measures to improve social disclosure need to be undertaken to ensure the Islamic banks fulfil their duties and obligations to their stakeholders and the society. As for the factors affecting social disclosure, only the age of Islamic banks was found to significantly affecting the extent of social disclosure. This may be due to older Islamic banks having the advantage of better insight on the market and stakeholders' needs and/or to strengthen their position in the industry. The results from this study shall contribute to a better understanding of the social disclosure performance of Islamic banks in Malaysia.